THE ROLE OF INTERNATIONAL LAW IN ADVANCING GENDER EQUALITY UNDER THE SUSTAINABLE DEVELOPMENT GOAL - Kumari Nitu; Tripathi, Manvendra Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper examines the role of international law in advancing gender equality under the framework of Sustainable Development Goal 5 (SDG 5). SDG 5, which aims to achieve gender equality and empower all women and girls, is a critical component of the United Nations 2030 Agenda for Sustainable Development. International law plays a pivotal role in promoting and enforcing gender equality through various treaties, conventions, and human rights instruments, such as the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) and the Universal Declaration of Human Rights (UDHR). This paper explores how these legal frameworks, combined with international bodies like the United Nations and regional institutions, contribute to setting normative standards, influencing national legislation, and driving global policy changes. Additionally, it assesses the progress and challenges faced by countries, with a particular focus on the Indian legal landscape, in implementing international commitments to gender equality. By analyzing current legal developments, the paper provides a comprehensive overview of how international law has both shaped and is being shaped by the pursuit of gender equality in line with SDG 5, offering insights into potential pathways for future advancements.